Speed of Venture Financing for Emerging Technology‐Based Entrepreneurial Firms as a Function of Founder Reputation. Issue 1 (13th February 2013) - Mahto, Raj V.; Khanin, Dmitry
<x xml:space="preserve">Abstract</x> One of the major commercialization hurdles for technology‐based entrepreneurial enterprises is financing and the speed of its acquisition. This is compounded in the case of emerging technology‐based enterprises by the nature of their technology acquisition and founding team structure. Many of these firms do not have founders with extensive reputations in the financial community. If founder reputation is important to funding sources with regard to speed and access, and emerging technology commercial development is important for solving twenty‐first‐century problems and generating economic growth, then there is cause for concern. Here we build on prior research and data from 140 Internet‐based firms to examine the effect that founder reputation has on the ability of an enterprise to swiftly obtain financing. Our results suggest that founder reputation expedites ventures' quick access to public but not to private financing. In addition, our results demonstrate that venture capital financing obtained early on and financing by large venture capital syndicates delay access to public financing for founders with extensive reputations.